The Role of Teachers in Developing Social Skills of Early Childhood Students at PAUD Shihabul Musthofa Merangkak, Embung Kandong Village, Academic Year 2024/2025 - Suhaini; Marniati (Formad English Foundation NTB-Jakarta, 2025)
This study aims to analyze the roles and strategies of teachers in developing the social skills of early childhood learners at PAUD Shihabul Musthofa, as well as to identify supporting factors and challenges faced during the learning process. The study employs a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results reveal that the teacher's role in developing children's social skills falls into the